Sinergitas Guru Dan Wali Murid Dalam Pendidikan Anak di Desa - Nur Laila Rahmawati; Fatya Nia Rahmawati; Alfi Nur Fadlillah; Andini Prastiwi; Ade Surya Lestari; Afida Nurmala (LP3M IAIFA Kediri, 2024)
Child education is a critical foundation for developing high-quality human resources. The synergy between teachers and parents plays a crucial role in supporting children's growth and education. Therefore, strengthening the relationship between them is essential to improving the quality of education at the community level. This community service project aims to identify factors influencing the synergy between teachers and parents and its impact on children's educational development in Semenkidul Village, Sukosewu District, Bojonegoro Regency. Additionally, the project seeks to implement the Asset-Based Community Development (ABCD) method to facilitate educational improvements in the village. The method employed is the ABCD approach, which involves five stages: inculturation, discovery, design, define, and reflection. Activities carried out include the Child Education Survey, Parenting: The Importance of Child Education, and consultation sessions between teachers and parents. The mentoring program encompasses five aspects of child education: moral education, academic education, social skills, creativity development, and environmental education. The results of this project indicate that through the ABCD approach, the Semenkidul community successfully identified the potentials and assets within their village. The synergy between teachers and parents was significantly strengthened, resulting in a positive impact on parents' understanding and involvement in their children's education. Consequently, this enhanced synergy has improved the quality of child education in the village.